A CRISPR-based approach using dead Cas9-sgRNA to detect SARS-CoV-2 - Aouida, Mustapha; Saifaldeen, Maryam; Al-Ansari, Dana E.; Taleb, Sara; Hssain, Ali Ait; Ramotar, Dindial (Frontiers in Molecular Biosciences, 2023)
Rapid, highly specific and robust diagnostic kits to detect viruses and pathogens are needed to control the spread and disease transmission globally. Of the many different methods proposed to diagnose COVID-19 infection, CRISPR based detection of nucleic acids tests are among the most prominent ones. Here, we describe a new way of using CRISPR/Cas systems as a rapid and a high specific tool to detect SARS-CoV-2 virus using the in-vitro dCas9-sgRNA-based technique. As a proof of concept, we used a synthetic DNA of the M gene, one of the SARS-CoV-2 virus genes, and demonstrated that we can specifically inactivate unique restriction enzyme sites on this gene using CRISPR/Cas multiplexing of dCas9-sgRNA-BbsI and dCas9-sgRNA-XbaI. These complexes recognize and bind to the target sequence spanning the BbsI and XbaI restriction enzyme sites, respectively, and protect the M-gene from digestion by BbsI and/or XbaI. We further demonstrated that this approach can be used to detect the M gene when expressed in human cells and from individuals infected with SARS-CoV-2. We referred to this approach as dead Cas9 Protects Restriction Enzyme Sites (dCPRES), and we believe that it has the potential to be applied as a diagnostic tool to many DNA/RNA pathogens.